Determinant Analysis of Stunting Incidence in Toddlers in Lubuklinggau City - Winda Lestari; Ida Samidah; Fiya Diniarti (Sean Institute, 2023)
WHO defines stunting in the Global Nutrition Targets 2025 as an irreversible growth disorder primarily driven by inadequate nutritional intake and infections that occur repeatedly in the first 1000 days of life. Reducing stunting rates is the primary goal of the six goals in the 2025 Global Nutrition Targets. Stunting is also a vital indicator of the second goal of sustainable development, namely, no hunger. As many as 149.2 million toddlers (22%) worldwide were stunted in 2020. Southeast Asia has as many as 10.8 million toddlers (13.9%). This study analyzes the determinants of toddler stunting in Lubuklinggau City in 2022. The method used is an analytic observational research design with a case-control approach. Data were collected using a questionnaire on 71 stunted respondents and 71 respondents who were not stunted through the Cluster Random Sampling technique. The population to be studied was divided into sub-populations (clusters). A sample was selected for each cluster by random sampling. The results of the bivariate analysis showed that the variables Gender, Low Birth Weight, History of Exclusive Breastfeeding, Maternal Age at Birth, Parents' Income, History of ANC, and History of Infectious Diseases had a significant relationship affecting the incidence of stunting in toddlers in Lubuklinggau City in 2022. The results of the multivariate analysis test also show that parents' income is the most dominant factor influencing toddler stunting incidence in Lubuklinggau City in 2022.